2016
DOI: 10.18632/oncotarget.10515
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index predicts the clinical outcome in patients with metastatic renal cell cancer treated with sunitinib

Abstract: BackgroundIn this retrospective analysis, we explored the prognostic and predictive value of the systemic immune-inflammation index (SII), based on lymphocyte, neutrophil, and platelet counts, at baseline and changes at week 6 during first-line sunitinib in patients with metastatic renal cell cancer (RCC).ResultsPatients were stratified into high SII (≥ 730) and low SII (< 730) groups. SII was associated with objective response, p < 0.0001. The median PFS was 6.3 months (95% CI 5.5–8.9) in patients with SII ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 28 publications
4
125
0
2
Order By: Relevance
“…Thrombocytosis and lymphopenia have also been associated with prognosis in metastatic RCC treated with first-line VEGF-targeted treatment (11,12). Systemic immune inflammation index (SII) combines these three parameters: neutrophils, platelets, and lymphocytes, and has been previously significantly associated with prognosis in several tumor types including metastatic RCC (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytosis and lymphopenia have also been associated with prognosis in metastatic RCC treated with first-line VEGF-targeted treatment (11,12). Systemic immune inflammation index (SII) combines these three parameters: neutrophils, platelets, and lymphocytes, and has been previously significantly associated with prognosis in several tumor types including metastatic RCC (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The systemic immune-inflammation index (SII), which uses a simple calculation based on peripheral lymphocyte, neutrophil, and platelet counts, was recently investigated as a prognostic marker in several tumours (van Soest et al, 2015;Bhindi et al, 2016;Lolli et al, 2016). In this issue of the British Journal of Cancer, two articles highlight for the first time the prognostic significance of SII in patients with GCT.…”
mentioning
confidence: 99%
“…In a recent retrospective series by Lolli et al, SII was identified as being a reliable parameter both as prognostic and predictive factor in RCC patients treated with sunitinib. Baseline SII values were independent factors for PFS and OS [114]. However, not all studies agree on the prognostic value of SII.…”
Section: Inflammation As Prognostic Factormentioning
confidence: 91%